2013
DOI: 10.3126/jkmc.v1i2.8143
|View full text |Cite
|
Sign up to set email alerts
|

The haemodynamic and ventilatory responses with I-gel, laryngeal mask airway and tracheal intubation during laparoscopic cholecystectomy

Abstract: Background: Despite use of adequate medications and techniques, tracheal intubation induces haemodynamic stress response, which can be minimized by using supraglottic airway devices instead of tracheal tube in elective surgical cases with adequate oxygenation and ventilation. Objectives: To compare haemodynamic variables and ventilation parameters of I-gel and laryngeal mask airway with tracheal intubation during laparoscopic surgery. Methods: This is a prospective randomized comparative study among 90 cases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…However the difference in MAP was not statistically significant after airway manipulation in all the three groups. [21] The reason for this difference might be Fentanyl, Propofol and Vecuronium used in the above study more effectively attenuates the stress response than Fortwin, Thiopentone and Atracurium used in our study. The results of studies conducted by Gauri Punjabi et al (2013) and Masoomeh Tabari et al (2013) are similar to our study.…”
Section: Blood Pressurementioning
confidence: 66%
See 1 more Smart Citation
“…However the difference in MAP was not statistically significant after airway manipulation in all the three groups. [21] The reason for this difference might be Fentanyl, Propofol and Vecuronium used in the above study more effectively attenuates the stress response than Fortwin, Thiopentone and Atracurium used in our study. The results of studies conducted by Gauri Punjabi et al (2013) and Masoomeh Tabari et al (2013) are similar to our study.…”
Section: Blood Pressurementioning
confidence: 66%
“…The heart rate increment was there at 3 min and 5 min after airway manipulation but the difference was not statistically significant. [21] Gauri Punjabi et al (2013) studied the cardiovascular changes subsequent to LMA insertion and found that mean pulse rate increased by 5-10/ min after LMA insertion and returned to baseline in 10 minutes. [22] In our study the mean rise in heart rate is 33/min but this difference can be due to the effect of Fentanyl, Propofol and Halothane used in the above study which can cause bradycardia.…”
Section: Changes In Mean Arterial Pressure At Various Time Intervalsmentioning
confidence: 99%
“…Similarly, Maharjan in 2012 observed that hemodynamic perturbations were maximum with tracheal intubation and moderate with laryngeal mask airway whereas stable hemodynamics were observed with I-gel. [ 4 ]…”
Section: Discussionmentioning
confidence: 99%
“…This study concluded that I-gel produced the least hemodynamic stress response while both supraglottic devices had acceptable ventilation parameters during laparoscopic surgery. [ 4 ] Suhitharan also conducted a similar study in 2013 comparing I-gel to LMA Supreme. [ 5 ] However, to our knowledge, there is a paucity of studies comparing I-gel and endotracheal intubation in pediatric patients undergoing laparoscopic surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…24 , they have compared haemodynamic variables of I-GEL and laryngeal mask airway with tracheal intubation during laparoscopic surgery. In their study there was increase in mean heart rate after use of airway device in all three groups, but maximum with tracheal tube and least with I-GEL.…”
Section: Discussionmentioning
confidence: 99%